Flavonoids as Prospective Neuroprotectants and Their Therapeutic Propensity in Aging Associated Neurological Disorders - Ayaz, Muhammad; Sadiq, Abdul; Junaid, Muhammad; Ullah, Farhat; Ovais, Muhammad; Ullah, Ikram; Ahmed, Jawad; Shahid, Muhammad (Frontiers in Aging Neuroscience, 2019)
Modern research has revealed that dietary consumption of flavonoids and flavonoids-rich foods significantly improve cognitive capabilities, inhibit or delay the senescence process and related neurodegenerative disorders including Alzheimer’s disease (AD). The flavonoids rich foods such as green tea, cocoa, blue berry and other foods improve the various states of cognitive dysfunction, AD and dementia-like pathological alterations in different animal models. The mechanisms of flavonoids have been shown to be mediated through the inhibition of cholinesterases including acetylcholinesterase (AChE), and butyrylcholinesterase (BChE), β-secretase (BACE1), free radicals and modulation of signaling pathways, that are implicated in cognitive and neuroprotective functions. Flavonoids interact with various signaling protein pathways like ERK and PI3-kinase/Akt and modulate their actions, thereby leading to beneficial neuroprotective effects. Moreover, they enhance vascular blood flow and instigate neurogenesis particularly in the hippocampus. Flavonoids also hamper the progression of pathological symptoms of neurodegenerative diseases by inhibiting neuronal apoptosis induced by neurotoxic substances including free radicals and β-amyloid proteins (Aβ). All these protective mechanisms contribute to the maintenance of number, quality of neurons and their synaptic connectivity in the brain. Thus flavonoids can thwart the progression of age-related disorders and can be a potential source for the design and development of new drugs effective in cognitive disorders.